Strategy for Implementing the Technical Functions of the Ministry of Defense in the Regions to Realize a Strong National Defense - Yudhi Murfi; Syaiful Anwar; Yoedhi Swastanto; Totok Imam Santoso; R Djoko Andreas Navalino; Robby Mochamad Taufik; Brantas Suharyo G; Arman Maulana (Journal of Law, Politic and Humanities, 2024)
This study aims to analyze the role and challenges in the implementation of the technical functions of the Ministry of Defense in the regions, as well as its contribution to a strong national defense system. In the context of Law Number 3 of 2002 concerning National Defense, this study highlights the importance of synergy between the central and regional governments in managing national defense. Through the literature study method, this study examines various regulations, the role of regional governments, the involvement of TNI units, and the use of technology in supporting regional defense strategies. The results of the study indicate that although there are supportive policies, there are still significant challenges in implementation in the field, including less than optimal coordination between the center and regions, and limited facilities and infrastructure. This study concludes that the integration of formulating regional defense strategies in collaboration between Ministry of Defense, TNI and regional governments is very important to realize a strong, adaptive and resilient national defense system in facing various threats.